Terapia nutricional via oral para tratamento te pacientes hospitalizados com Covid-19 no Hospital Regional de Araguaína - Alcântara, Julia Milhomem Neves (Universidade Federal do Tocantins, 2023)
Covid 19, originating from the new coronavirus (SARS CoV 2), has impacted humanity since the second half of 2019, having its c ontamination status raised to a pandemic, by the WHO, in 2020. In this context, the objective of the study is to know the clinical practice of oral nutritional therapy for the treatment of patients hospitalized with Covid 19 at the Hospital Regional de Ara guaína, Tocantins, regarding the length of stay. A research was carried out with patients over 18 years of age, with moderate to severe clinical manifestations due to this condition, who sought the HRA to receive necessary treatment from April to August 20 20. During the research, descriptive analyzes were carried out with data from 165 patients, meeting the inclusion criteria, 90 (54.5%) males and 75 (45.5%) females, the majority of mixed race 136 (84%). Regarding the outcomes, 99 (60%) died, 46 (27.9%) wer e discharged and 20 (12.1%) were transferred to other institutions. The percentage of consistencies of the diets and changes in nutrients received in the three periods of hospitalization, initial time (T0), time seven (T7) and final time (Tfi) were also an alyzed. Where, it was analyzed that zero predominated in T0, with 27 (16.4%), free in T7 with 24 (14.5%) and mild in Tfi with 20 (12.1%). There were no significant data for high protein diets or oral supplements. The study had limitations given the difficu lties related to data collection, highlighting the importance of nutritional action directly with the patient, ensuring better treatment of patients hospitalized with Covid 19 and greater knowledge of data.